Contrast-enhanced ultrasound quantifies the perfusion within tibial non-unions and predicts the outcome of revision surgery - Krammer, Daniel; Schmidmaier, Gerhard; Weber, Marc-André; Doll, Julian; Rehnitz, Christoph; Fischer, Christian (Ultrasound in medicine & biology, 2018)
Vascularity is one of the factors determining successful bone regeneration. This prospective study focused on quantifying the microperfusion of tibial non-unions with contrast-enhanced ultrasound (CEUS) 12 wk after revision surgery and comparing it with the osseous consolidation at a maximum of 24 mo assessed with standard radiography and computed tomography. Of 36 patients with tibial non-unions, 28 (77.8%) manifested consolidation, and 8 patients required further revision surgery. CEUS revealed significantly higher perfusion in consolidated versus persistent non-unions for all quantification parameters (e.g., wash-in perfusion index p = 0.036). Receiver operating characteristic analysis revealed a sensitivity of 82.1% and specificity of 75.0% with a wash-in perfusion index cutoff at 19.9 a.u. for diagnosing persisting non-unions. More than 1 y ahead of the final radiologic diagnostic examination, CEUS could predict eventual consolidation based on the osseous perfusion as soon as 12 wk postoperatively. This information can be crucial for the decision-making process for re-revision at an early stage.